Lymphadenectomy and margin‐negative resection for biliary tract cancer surgery in the United States—Differential technical performance by approach. Issue 4 (16th May 2022) - Kim, Bradford J.; Newhook, Timothy E.; Tzeng, Ching‐Wei D.; Ikoma, Naruhiko; Chiang, Yi‐Ju; Chun, Yun Shin; Vauthey, Jean‐Nicolas; Tran Cao, Hop S.
Abstract: Background: As minimally invasive surgery (MIS) approaches to biliary tract cancers become more commonplace, understanding the adequacy of their oncologic performance is key. Methods: The National Cancer Database 2010–2016 was queried for patients who underwent hepatectomy for intrahepatic cholangiocarcinoma (IHC) and T1b or more advanced gallbladder cancer (GBC). Patients were grouped by approach: open (OA), laparoscopic (LA), and robotic (RA). Margin status, rate of lymph node (LN) dissection, and yield of LN dissection were evaluated. Results: This cohort of 8612 patients, including 4034 patients with IHC (OA: 3281, LA: 675, RA: 78) and 4578 patients with GBC (OA: 1893, LA: 2588, RA: 97), MIS was used 40% of the time. R0 resection was achieved in 82% OA, 84% LA, and 91% RA, p  = 0.004. Rate of LN dissection was 53% (OA: 60%, LA: 42%, RA: 51%, p  < 0.001). Among patients who underwent lymphadenectomy, 6 + LN were retrieved less commonly with a LA (OA: 27%, LA: 20%, and RA: 30%, p  < 0.001). High‐volume MIS hepatectomy centers were more likely to perform a lymphadenectomy (odds ratio [OR]: 1.41) and a sampling of 6 + LN (OR: 1.18). Conclusion: Regardless of approach, lymphadenectomy is underperformed nationwide for biliary tract tumors, particularly with LA. As the use of MIS grows for the treatment of biliary tract cancers, scrutiny of oncologic outcomes is required.